Clinical and economic impact of COVID-19 on people with obesity in a Spanish cohort during the first pandemic peak - M, Torrego-Ellacuría; MA, Rubio-Herrera; B, González López-Valcárcel; ME, Fuentes-Ferrer; V, Martín; F, Poyato; P, Barber-Pérez; C, Santucci; A, Nuñez; C, González-Pérez; M, Luaces (Frontiers in Endocrinology, 2023)
COVID-19 and obesity relationship has been extensively studied since the COVID-19 outbreak, proving obesity is a risk factor. This study aims to broaden the available information about this association and to evaluate the economic impact of obesity and the COVID-19 disease combination. This retrospective study analyzed a sample of 3,402 patients admitted to a Spanish hospital with available body mass index (BMI) data. The prevalence of obesity was 33.4%. Patients with obesity showed a higher risk of hospitalization (OR 95% Confidence Interval [CI]=1.46; [1.24-1.73]; p < 0.001), which increased with the obesity degree (I: OR [95% CI]=1.28 [1.06-1.55], p =0.010; II: OR [95% CI]=1.58 [1.16-2.15], p =0.004; III: OR [95% CI] =2.09 [1.31-3.34], p =0.002). Patients with type III obesity had a significantly higher risk of intensive care unit (ICU) admission (OR [95% CI]= 3.30 [1.67-6.53]; p = 0.001) and invasive mechanical ventilation (IMV) need (OR [95% CI]= 3.98 [2.00-7.94]; p<0.001). The average cost per patient was remarkably higher in patients with obesity (p = 0.007), reaching an excess cost of 28.41% in the study cohort and rising to 56.5% in patients < 70 years. The average cost per patient increased significantly with the degree of obesity (p = 0.007). In conclusion, our results suggest a strong association between obesity and adverse COVID-19 outcomes and higher expenditures in patients with both conditions.